1998
DOI: 10.1021/js980087a
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution of Radiolabeled Lipid–DNA Complexes and DNA in Mice

Abstract: The tissue biodistribution and expression of [33P]DNA-1-[2-[9-(Z)-octadecenoyloxy]ethyl]]-2-[8](Z)-heptadece nyl]-3 -[hydroxyethyl]imidazolinium chloride (DOTIM):cholesterol complexes and 33P-radiolabeled DNA expressing chloramphenicol acetyl transferase (CAT; 4.7 kB) were studied after intravenous (iv) injection in ICR mice. Mice were injected with 200 microL of complex containing DNA at 3 mg/kg or DNA alone. One group received 8 microCi of radioactivity and were sacrificed at 5 and 20 min, and 1, 2, 4 and 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
65
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(65 citation statements)
references
References 16 publications
0
65
0
Order By: Relevance
“…It has been reported that incubation in pure serum or serum-containing media could decrease the extent of lipoplex delivery and alter its intracellular fate 19,20) and even cause the lipoplex to disintegrate upon prolonged exposure. 18,21) However, an injected lipoplex is rapidly cleared from the circulation 18,22) and internalized in the lungs, 23) thus ruling out long-term exposure to serum. In addition, Sakurai et al showed the pre-incubation of a DOTAP/Chol lipoplex with serum for as long as 30 min did not significantly impair lipofection in the lungs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that incubation in pure serum or serum-containing media could decrease the extent of lipoplex delivery and alter its intracellular fate 19,20) and even cause the lipoplex to disintegrate upon prolonged exposure. 18,21) However, an injected lipoplex is rapidly cleared from the circulation 18,22) and internalized in the lungs, 23) thus ruling out long-term exposure to serum. In addition, Sakurai et al showed the pre-incubation of a DOTAP/Chol lipoplex with serum for as long as 30 min did not significantly impair lipofection in the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…5). The first pass entrapment (60-80% of the liposomes are entrapped within minutes after intravenous injection) 18,22,28) can be attributed to the highly extended lung capillary bed and was proposed to explain the predominant gene expression in the lungs. 28,29) Ito et al 30) recently reported that vascular endothelial cells, probably under angiogenesis, in the lungs of tumor bearing mice, which demonstrates an increased uptake of cationic liposome-DNA complexes and transgene expression compared to normal mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was interesting to find that both chitosan and chitosan oligosaccharide can not only influence the particle shape and morphology but enhance the dispersibility of spray-dried powders. Chitosan oligosaccharide, possessing the properties of soluble, biodegradable, biocompatible, bioadhesive and nontoxic, 38) has the ability to enhance mucosal absorption by opening tight junctions, 39) potentially resulting in an increase of drug absorption subsequent to inhalation. In our study, the addition of chitosan oligosaccharide in formulations can achieve higher spray-dried yields (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Since free oligonucleotides and DNA are rapidly degraded by serum nucleases, 4) many efforts are focused on developing the carriers to protect and deliver these materials into targeted cells. Two delivery systems namely viral and non-viral vectors are currently developed to solve the problems.…”
mentioning
confidence: 99%